Brainstem Biomarkers of Clinical Variant and Pathology in Progressive Supranuclear Palsy. Issue 4 (31st December 2021) - Grijalva, Rosalie M.; Pham, Nha Trang Thu; Huang, Qiao; Martin, Peter R.; Ali, Farwa; Clark, Heather M.; Duffy, Joseph R.; Utianski, Rene L.; Botha, Hugo; Machulda, Mary M.; Weigand, Stephen D.; Ahlskog, J. Eric; et al.
Abstract: Background: Magnetic resonance brainstem measurements are useful structural biomarkers in the Richardson's syndrome variant of progressive supranuclear palsy (PSP). However, it is unclear how these biomarkers differ across the phenotypic spectrum of PSP and how they relate to underlying pathology. Objective: The aim of this study was to compare brainstem imaging measures across clinical variants of PSP and determine sensitivity and specificity based on pathologically diagnosed cases. Methods: A total of 153 patients with PSP who represented eight clinical variants were recruited at Mayo Clinic (Rochester, MN, USA) and underwent structural magnetic resonance imaging (MRI). Midbrain and pons area and superior and middle cerebellar peduncle width measurements were performed, and midbrain/pons ratio and Magnetic Resonance Parkinsonism Index (MRPI) were calculated. Among the 43 patients who later died, PSP pathology was confirmed in 29, whereas 14 had other pathology. Results: Brainstem measurements varied across PSP clinical variants and were most abnormal in PSP‐Richardson's syndrome and frontal variants, followed by PSP‐corticobasal, PSP‐speech/language, and PSP‐parkinsonism variants. All these variants showed abnormalities compared with controls. The PSP‐gait freezing variant and patients with prominent corticospinal tract signs showed normal brainstem measures. Among cases with confirmed PSP pathology, the midbrain area, midbrain/pons ratio, and MRPI were all more abnormal compared to those with other pathologies, with best differentiation obtained with the MRPI (sensitivity = 83%; specificity = 85%). Conclusions: MRI brainstem measures show utility as diagnostic biomarkers across PSP clinical variants and have the potential to be useful in predicting underlying pathology. © 2021 International Parkinson and Movement Disorder Society